Red hat certified specialist in containers and Kubernetes (EX180) and OpenShift administration (EX280) (video collection). (Pearson IT Certification, 2022)
Overview All topics covered to pass the EX180 and EX280 exams. 16+ Hours of Video Instruction Description This master class includes the following courses: Red Hat Certified Specialist in Containers and Kubernetes Complete Video Course: Red Hat EX180 Red Hat OpenShift Administration: Red Hat EX280 Red Hat Certified Specialist in Containers and Kubernetes Complete Video Course: Red Hat EX180 provides an in-depth analysis of the core objectives and topics in the Red Hat EX180 exam so you can get started with containers on Red Hat Enterprise Linux and OpenShift, the Red Hat Kubernetes distribution, while also preparing for the Red Hat exam EX180. Topics include managing containers and container images with Podman, running applications in OpenShift, and using OpenShift to automate complex automation builds. This video course is also a great resource for anyone interested in working with standalone containers using Podman on Red Hat, as well orchestrated containers and devops workflows using Red Hat OpenShift. In almost 9 hours of engaging video training, instructor Sander van Vugt uses deep-dive explanations, whiteboard instruction, and real-world hands-on demos. Each lesson concludes with a hands-on lab, which provides a deeper understanding of all the topics of Red Hat Certified Specialist in Containers and Kubernetes and helps you excel on your EX180 exam. Red Hat OpenShift Administration Complete Video Course: Red Hat EX280 provides an introduction in administrating OpenShift and prepares viewers to take the Red Hat exam EX280. This course provides in-depth training and hands-on labs exploring the ins and out of administering in OpenShift. Topics include management of cluster nodes, users, and role-based access control, as well as management of applications in an OpenShift environment. The Red Hat Certified Specialist in OpenShift Administration exam (EX280) tests the knowledge, skills, and ability to create, configure, and manage a cloud application platform using Red Hat OpenShift Container Platform. This engaging self-paced video training solution provides learners with more than 8 hours of video instruction from an expert trainer with years of providing practical Linux teaching experience. Through the use of topic-focused instructional videos, you will gain an in-depth understanding of all topics on the Red Hat OpenShift Administration EX280 exam, as well as a deeper understanding of Ansible. The combination of video and labs provides a unique offering that gives you a full toolkit to learn and excel on your exam. Course Requirements One (virtual) machine running Red Hat Enterprise Linux, CentOS, or Rocky Linux 8.x to perform the labs about Podman containers A computer running any operating system with at least 16GB RAM to run the CodeReady Containers Virtual Machine Students should be able to run a virtual machine that requires 12GB of RAM About Pearson Video Training Pearson publishes expert-led video tutorials covering a wide selection of technology topics designed to teach you the skills you need to succeed. These professional and personal technology videos feature world-leading author instructors published by your trusted technology brands: Addison-Wesley, Cisco Press, Pearson IT Certification, Sams, and Que. Topics include IT Certification, Network Security, Cisco Technology, Programming, Web Development, Mobile Development, and more. Learn more about Pearson Video training at http://www.informit.com/video.